Resistance of the Collateral Ligaments of the Femorotibial Joint in Domestic Dogs (Canis lupus familiaris LINNAEUS, 1758) - Faria, M. D.; Regis, L. O.; Gradela, A.; Constantino, A. C.; Olivier, N. C.; Pereira Neto, J. (Journal of Morphological Sciences, 2018)
Introduction This work aimed to demonstrate the resistance of the femoral-tibial joint collaterals of 60 dogs of undefned breed, euthanized at the Zoonoses Control Centre of the city of Petrolina (PE), North-Eastern Brazil.Materials and Methods The femur-tibial articulation was dissected to expose the collateral ligaments. Bones were cut on the distal third of the femur and the proximal third of tibia and fibula. The knee joint was kept bound only by the collateral ligaments and then submitted to destructive mechanical tests, evaluating the deformation of the ligaments (mm) per unit of time, (seconds), and the joint resistance.Results We could observe no side effects of contralateral joints. In a destructive mechanical assay, we detected that the medial collateral ligaments ruptured earlier than the lateral ones. The resistance of the lateral and medial ligament of the right limb of females was respectively 537.1N ± 413.6 and 360.1N ± 228.6; while in males, were of 632.4N ± 333.4 e 440.4N ± 227.1. About the left antimere, the females presented 442.4N ± 288 resistance on the lateral ligament and 417.4N ± 190.6. In males, the resistance was 605.8N ± 316.1 e 548.6N ± 2,333.7, respectively.Conclusion The results of our research will allow the development of synthetic tissues to replace the natural ligament of dogs in cases of rupture or degeneration.
Keywords: arthrology; material resistance; knee